OPTIMIZACIÓN DE PARÁMETROS DE REGLAJE PARA MEJORAR LA EFICIENCIA DE MÁQUINAS INYECTORAS DE TERMOPLÁSTICOS - MITE VILLACRES, DIEGO ALONSO (2015)
This report details the improvements in a company processor of plastic located in the city of Guayaquil, focused especially in the field of the thermoplastic injection where it is observed that you scheme them modern thermoplastic injectors they allow its calibration from a control panel; but as for its handling the operatives don't have any knowledge initially of how to carry out it, this originates that he/she learns empirically on its operation and operation, that which bears at long time of outburst of machines. During the development of the project of optimization of setting parameters to improve the efficiency of machines injectors you achievement to reduce the time of machine outburst, cycle and the volume of produced scrap for machine regulation applying an easy and simple mathematical method To be able to apply this method he/she was carried out an analysis of the taken data (raw material and regulation parameters) of the 8 selected molds, registered in the technical records, it stops then to calculate the injection parameters and to carry out the respective tests working in parallel with the operator in each machine outburst. Finally he/she was carried out an analysis of the obtained results, to see the advantages that it is obtained by adjustments aleatory vs good adjustments.